Sosialisasi Pendidikan Kesehatan Menggunakan Video Animasi Terhadap Peningkatan Pengetahuan Wanita Usia Subur (WUS) Tentang IVA Test di Klinik Pratama Jannah - Fitriyani Pulungan; Yusniar Siregar; Tri Marini (Pusat Riset dan Inovasi Nasional, 2023)
Based on the Health Profile of Deli Serdang district in 2019 in North Sumatra, early detection examinations were 4.59%, while Indonesia's target achievement was 7.34% and from data on early detection of cervical cancer coverage in Deli Serdang district, 285 positive IVA cases were found. On this basis, the author carries out community service with the aim of providing insight to the Pratama Jannah Clinic, Deli Serdang Regency so that they know about the IVA Test for early detection of cervical cancer and the process of carrying out the IVA Test and can share the knowledge gained with other women in their environment. The methods used in this community service are lecture, question and answer methods and with the help of videos. After carrying out this community service, it was found that there was an increase in the knowledge of women of childbearing age from before it was carried out and after the socialization about the IVA Test using Animation Video at Klink Pratama Jannah, Deli Serdang Regency had increased, the author also made educational aids in the form of animated video material.